Assessment of Cargo Delivery Quality Using Fuzzy Set Apparatus - Kyrychenko, Hanna; Statyvka, Yurii; Strelko, Oleh; Berdnychenko, Yulia; Nesterenko, KHalyna (International Journal of Engineering and Technology, 2018)
The influence of the existing operation conditions for the time of cargo transportation, i.e. ferrous metals to the port station, was investigated. It was proposed to carry out the management of cargo delivery on the basis of determining the values of cargo handling duration while implementing the stages of the schedule. It was proposed to carry out assessment of the delivery process, including transportation using the fuzzy set apparatus. To determine the quality of transportation, an ordered categorized scale of values of the duration of cargo's staying in certain conditions at delivery stages was proposed. The assessment of deviations at all the stages of transportation with the use of linguistic definitions of conditions allows quantifying such an indicator as the transportation quality. The characteristics of deviations during transportation are provided in the linguistic form to the dispatching unit for making a decision. The revealed regularities in deviations from the standard schedules of trains during delivery of cargos are an objective basis for taking into account them in the mathematical models of the forecast of time of cargo delivery at each of the defined stages of transportation. The data on the forecasted and actual transportations are accumulated in the existing information base, forming data files for assessing the quality of the transportation process, the adequacy of the mathematical model and correcting of the model in case of significant organizational or technical changes.Â